(untitled) (Global Journal of Human-Social Science, 2021)
The interaction between the health emergency and the available technology produces an extraordinary metamorphosis of social and economic customs. This energy has released an intense centrifugal force that has displaced activities and people quickly and radically, with strong consequences on the structure of cities. To properly metabolize these changes, adequate cultural processing and specific services are needed.